Respuesta :

Answer:

y = [tex]\frac{a^2-ab}{a+1}[/tex]

Step-by-step explanation:

a - y = b + [tex]\frac{y}{a}[/tex] ( multiply through by a to clear the fraction )

a² - ay = ab + y ( subtract y from both sides )

a² - ay - y = ab ( subtract a² from both sides )

- ay - y = ab - a² ← factor out y from each term on the left side

y(- a - 1) = ab - a² ( divide both sides by - a - 1 )

y = [tex]\frac{ab-a^2}{-a-1}[/tex] ( multiply numerator/ denominator by - 1 )

y = [tex]\frac{a^2-ab}{a+1}[/tex]